Mobiliário infantil: conceito de uma cama Montessori - Batista, Fernanda Gasparoti [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present research is based on Montessori pedagogical methodology. Created by Maria Montessori, this is a set of theories, practices and didactic materials. According to Montessori, the most important fact is not the material or the practice, but the possibility of developing the child's abilities from the evolution of each. From this, the proposal is the development of a children's furniture - a bed - from the study proposed by Montessori, considering characteristics of child development, children's furniture and ergonomics. The projects a product that contributes to the child developing in its ‘natural time’ with freedom and autonomy.

A presente pesquisa tem base na metodologia pedagógica montessoiana. Criada por Maria Montessori, trata-se de um conjunto de teorias, práticas e materiais didáticos. De acordo com Montessori, o fato mais importante não é o material ou a prática, mas a possibilidade do desenvolvimento das habilidades da criança a partir da evolução de cada um. A partir disso, a proposta é o desenvolvimento de um mobiliário infantil – uma cama – a partir do estudo proposto por Montessori, considerando características do desenvolvimento infantil, mobiliário infantil e ergonomia. O projeto é de um produto que contribua para que a criança se desenvolva em seu “tempo natural” com liberdade e autonomia.
Children's furniture: a Montessori bed concept
Keywords: Montessori method; Child development; Children's furniture; Método Montessori; Desenvolvimento infantil; Mobiliário infantil